Maternal mortality from postpartum hemorrhage: an integrative literature review (Research, Society and Development, 2022)
Objective: to describe the scientific production on maternal mortality due to postpartum hemorrhage (PPH) from the indexed literature. Method: qualitative research of integrative literature review with thematic analysis, as proposed by Minayo (2004). The search for articles was conducted in the portal of BVS Brazil (Virtual Health Library), and in the SciELO (Scientific Electronic Library Online), LILACS databases with the strategy: Postpartum hemorrhage AND Obstetrics AND Maternal mortality AND Emergency treatment, listing studies between the years 2015 and 2020. Results: after the selection of articles, it was possible to reach a sample of 07 papers identified in three thematic categories: 1 the knowledge about postpartum hemorrhage; 2 management for prevention of related complications; 3 epidemiological information. Conclusion: it was identified that there is a need for greater knowledge of professionals on PPH and among the managements for prevention of complications, it is cited the tamponade with uterine balloon and intravenous hydration, finally it is highlighted that there is a scarcity in the literature on the subject.